The Reflective Parent Effect: Rethinking Early Childhood Development Through Self Aware Parenting (A Systematic Literature Review) - Ririn Despriliani; Najiatul Pikria; Nayla Luthfia Salwa (Riviera Publishing, 2026)
This study was motivated by the crucial role of parents during early childhood, a developmental period in which many parenting practices remain non-reflective. The objective of this study was to analyze the concept of self-aware parenting and its influence on early childhood development. The methodology employed a Systematic Literature Review (SLR) using data sources from Google Scholar, Scopus, and ERIC, with inclusion and exclusion criteria based on PRISMA guidelines. The findings indicated that self-aware parenting significantly contributed to children’s socio-emotional, cognitive, and behavioral development through emotional regulation, parenting sensitivity, and the quality of parent–child interactions. The discussion revealed that parental reflective capacity served as a protective factor that supported children’s psychological development and reduced the risk of behavioral problems. The Reflective Parent Effect mechanism explained the relationship between parents’ internal reflection, interaction quality, and multidimensional developmental outcomes. In conclusion, parental self-awareness represents a fundamental foundation for creating a healthy and supportive parenting environment, highlighting the importance of strengthening reflective capacity in early childhood education.